2022
DOI: 10.1186/s13045-022-01270-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel tRNA-derived fragment AS-tDR-007333 promotes the malignancy of NSCLC via the HSPB1/MED29 and ELK4/MED29 axes

Abstract: Background Transfer RNA-derived fragments (tRFs) are a new class of small non-coding RNAs. Recent studies suggest that tRFs participate in some pathological processes. However, the biological functions and mechanisms of tRFs in non-small cell lung cancer (NSCLC) are largely unknown. Methods Differentially expressed tRFs were identified by tRF and tiRNA sequencing using 9 pairs of pre- and post-operation plasma from patients with NSCLC. Quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…measured plasma AS-tDR-007333 levels and found that they were significantly higher in NSCLC patients than in healthy controls. The study further revealed that the AUC for AS-tDR-007333 was 0.9379, which suggests that AS-tDR-007333 can serve as a diagnostic biomarker for NSCLC ( 28 ). Enlightened by previous research carried out by Yang et al., we screened and identified tRF-55:76-Tyr-GTA-1-M2 and tRF-1:29-Pro-AGG-1-M6 as potential biomarkers with high diagnostic sensitivity and specificity in LUAD patients.…”
Section: Discussionmentioning
confidence: 85%
“…measured plasma AS-tDR-007333 levels and found that they were significantly higher in NSCLC patients than in healthy controls. The study further revealed that the AUC for AS-tDR-007333 was 0.9379, which suggests that AS-tDR-007333 can serve as a diagnostic biomarker for NSCLC ( 28 ). Enlightened by previous research carried out by Yang et al., we screened and identified tRF-55:76-Tyr-GTA-1-M2 and tRF-1:29-Pro-AGG-1-M6 as potential biomarkers with high diagnostic sensitivity and specificity in LUAD patients.…”
Section: Discussionmentioning
confidence: 85%
“…In this study, we find that tRF-5c were the most abundant categories in pig spleen. Previous studies showed that the class of tsRNA in stomach [ 59 ], lung [ 60 ] and plasma [ 61 ] were mainly tRF-5c. However, other results were also reported tiRNAs were primarily observed in ovary [ 62 ] and thyroid [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate the potential value of tRFs as therapeutic agents (98). In the context of oncogenic tRFs, the inhibition of certain tRFs may have therapeutic effects on cancer (99). Yang et al demonstrated that upregulation of AS-tDR-007333 significantly promoted the growth and migration of non-small cell lung cancer cells (99).…”
Section: Trfs As Therapeutic Agents or Targets For Cancer Therapymentioning
confidence: 98%
“…In the context of oncogenic tRFs, the inhibition of certain tRFs may have therapeutic effects on cancer (99). Yang et al demonstrated that upregulation of AS-tDR-007333 significantly promoted the growth and migration of non-small cell lung cancer cells (99). A mechanistic study revealed that AS-tDR-007333 and HSPB1 synergistically enhance transcription of mediator complex subunit 29 (MED29) by modifying histone modifications on MED29 promoter regions.…”
Section: Trfs As Therapeutic Agents or Targets For Cancer Therapymentioning
confidence: 99%